PARENTING STYLE, TIPE KEPRIBADIAN DAN PRESTASI AKADEMIK MAHASISWA PAI ANGKATAN 2015 IAIN CURUP - Mustar, Saidil (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2021)
This study aims to determine the effect of parenting style and personality types on the academic performance of PAI students of the 2015 IAIN Curup class. This research is quantitative descriptive. The results of this study are the first good parenting style because tcount= -1.12 is between ttable that is -2.63 and 2.63. Both personality types are good because tcount= 0.40 is between ttable that is -2.63 and 2, 63, The three academic achievements are very high because tcount = 3.08 is greater than ttable that is -2.63 and 2.63. fourth, there is a positive influence between parenting style on personality types because rcount = 0.432 is greater than rtabel 1% level = 0.1956, fifth, there is a positive influence between parenting style on academic achievement because rcount = 0.432 is greater than rtable level 1% = 0 , 1956, Sixth there was a positive influence between personality types on academic achievement because rcount = 0.52 is greater than rtable of 1% = 0.1956. seventh, there is a positive influence between parenting style and personality type together on academic achievement because rcount = 0.58 is greater than rtable of 1% = 0.1956.